Strategi Pembelajaran Tematik Untuk MeningkatkanPartisipasi Warga Belajar Paket A - Erma Nurmiati; Rudi Ruhardi (Institut Studi Islam Muhammadiyah Pacitan, 2025)
The Paket A equivalency education program is a non-formal learning service for individuals whohave not completed primary education. One of its main challenges is the low level of learnerparticipation, both in attendance and engagement during learning activities. This study aims toexamine thematic learning as an approach that can increase learner participation in Paket A. Theresearch method used is a literature study by reviewing previous research and theories related tothematic learning and equivalency education. The findings show that thematic learning can enhancelearner motivation, increase attendance, and encourage active involvement in discussions andclassroom activities. This approach aligns with andragogical principles, as it incorporates learners’life experiences into the learning process. However, its implementation continues to face obstacles,including limited tutor competence and insufficient learning facilities. This study concludes thatthematic learning has the potential to be an effective strategy to improve learner participation andlearning quality in Paket A.